ADVANTAGES OF PEDAGOGICAL SOFTWARE TOOLS - Nazokat Yusufjonova (Scholar Express Journal, 2025)
This article explores the advantages of pedagogical software tools in enhancing the effectiveness of the educational process in the digital era. It emphasizes the role of Learning Management Systems (LMS) and mobile applications in creating interactive learning materials that improve student engagement and academic outcomes. The study analyzes the principles, stages, and challenges of integrating digital tools into teaching practices. The findings support the pedagogical value of digital solutions for fostering dynamic, learner-centered instruction
Keywords: Pedagogical software tools; Learning Management System